Recently discovered early medieval grave from Serbin - Sokolov, Pavel; Gulyás, Bence (Dissertationes Archaeologicae, 2024)
An early medieval burial was found in Serbin (Krasnodar Krai, Slaviansk-na-Kubani District, Russia) in 2023. The grave contained a battle knife, analogies to which are known not only from Eastern Europe but also Inner Asia and Southern Siberia, emphasizing the vivid connections maintained throughout the Eurasian steppe in the second half of the first millennium AD. Grave 2023/3 of Serbin could be dated to the second half or last third of the 7th century AD.